2016
DOI: 10.4209/aaqr.2015.06.0407
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Measurements of High Pollutant Concentration Events in the Free Troposphere over the West Coast of South Korea between 1997 and 2011

Abstract: Aircrafts enable the direct measurement of chemical components in the free troposphere (FT). This study employed airborne measurements to examine the occurrences of high concentrations of SO 2 and NO x in the FT over the coastal region west of the Seoul metropolitan area, South Korea. The data from a long-term (1997-2011) airborne measurement campaign were used to determine the meteorological conditions favorable for carrying these pollutants into the Seoul area. The back trajectory analyses of 21 instances of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…The present result indicates that the complex terrain ventilation effect, as well as the cold front and low pressure synoptic conditions are most significant to the ABL‐FT exchange. These are consistent with the results of previous researches conducted in Europe, North America, and East Asia (Donnell et al., 2001; Lee et al., 2016; Lu & Turco, 1994; Oshima et al., 2013). Quantitatively, our correspondent exchange flux agrees to that calculated by Kiley and Fuelberg (2006) under the frontal system in the eastern United States (0.013 kg m −2 s −1 vs. 0.011 kg m −2 s −1 ).…”
Section: Summary and Discussionsupporting
confidence: 93%
“…The present result indicates that the complex terrain ventilation effect, as well as the cold front and low pressure synoptic conditions are most significant to the ABL‐FT exchange. These are consistent with the results of previous researches conducted in Europe, North America, and East Asia (Donnell et al., 2001; Lee et al., 2016; Lu & Turco, 1994; Oshima et al., 2013). Quantitatively, our correspondent exchange flux agrees to that calculated by Kiley and Fuelberg (2006) under the frontal system in the eastern United States (0.013 kg m −2 s −1 vs. 0.011 kg m −2 s −1 ).…”
Section: Summary and Discussionsupporting
confidence: 93%
“…On large scale, the warm conveyor belt associated with frontal cyclones is the main mechanism of ABL vertical ventilation (Brown et al., 1984; Ding et al., 2009; Eckhardt et al., 2004). And the developing low‐pressure systems can also uplift air pollutants from the surface into the FT (Lee et al., 2016). Conversely, anticyclone circulation tends to cause downward transport (Sinclair et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Also, ABL-FT vertical exchange is active in this region due to the unique topography (with mountains to the west/northwest and coastline bordered to the east) and special geographical location (mid-latitude westerlies accompanied by diverse weather processes), as Jin et al (2021) indicated. Many observational and modeling studies have shown that the NCP could be an effective source area for long-range air pollutant transport above the ABL height, and discussed its impact on downstream regions such as the Yangtze River Delta (YRD) (Kang et al, 2019), Northeast China (NEC) (Ding et al, 2009;Sun et al, 2022), Japan (JAP) and South Korea (KOR) (Lee et al, 2016;Uno et al, 2017), and even the Trans-Pacific regions (Liu et al, 2003;Oshima et al, 2013). Most of these works are limited to the descriptions of short-term cases.…”
mentioning
confidence: 99%
“…The driving reason behind the interest is the effect of elevated levels of NO 2 in Korea on human health (Kim and Song, 2017 and references therein). Measurements of NO 2 from aircraft have been used to obtain altitude profiles to compare with data obtained from fixed site measurements and to obtain a national scale estimate of pollutant exposure (Lee et al, 2016;Kim and Song, 2017).…”
mentioning
confidence: 99%